Edukasi Dampak Covid-19 Melalui Komik serta Pembagian Masker dan Sembako bagi Masyarakat Terdampak Covid-19 di Kelurahan Panjehang Kota Palangka Raya - Srie Rosmilawati; Mita Sari; Sirojul Rahman; Yustin Yustin; Isti Qomah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
Countries in the world face a big challenge in handling the coronavirus outbreak, which is officially identified by WHO as Corona Virus Disease-19 or abbreviated as Covid-19. This pandemic, which started in the city of Wuhan, China, has caused a global shock because, in the last few decades, we have never experienced a viral outbreak with such a rapid and massive rate and transmission rate like this coronavirus, far above its cousins ​​SARS and MERS viruses as well as Ebola, which had been tormented a few years ago, but was quickly resolved. Educational action on the impact of Covid-19 is very much needed to provide understanding to the people of Panjehang Village where the education contains what Covid-19 is, its effects and dangers, and how to prevent the spread of Covid-19 and to continue the distribution of food packages.